Mental rotation of tactic board instructions in basketball: Domain-specific expertise improves on-court performance - Krause, D.; Weigelt, M. (Research Quarterly for Exercise and Sport, 2023)
Purpose: In basketball, tactical instructions are presented on tactic boards under temporal constraints (e.g., time-outs). Based on the disparity in the orientation of the tactic board and the players` egocentric on-court visual perspective, there are high affordances in visual-spatial transformation (e.g., mental rotation), which impede information processing and decrease execution accuracy. The aim of this study was to scrutinize how the effect of different orientations of visual tactical displays on information processing demands and execution accuracy is affected by expertise in basketball.